Power and Resistance in the Neoliberal Age - Valerio Lastrico (Coordinamento SIBA, 2016)
Aim of this work is trying to show, from a mainly theoretical standpoint but with constant ref-erences to Italian concrete cases, how neoliberalism, even though usually described as a State withdrawal from many issues left to individuals’ freedom, would actually represent an increase in forms of State inter-vention and control. The paper aims to analyze what forms this control may take, starting from current economic crisis, finding they are attributable to two scenarios: an explicit centralizing form, analyzed through the analytical tools of "state of exception" literature (Schmitt, Agamben); an implicit technical form, studied referring to the literature on "government through numbers" (Porter, Power, Miller, Es-peland, Desrosier). The paper also tries to show, once again through concrete examples, and by compari-son with Polanyi’s analysis of resistance to ‘900 classical liberalism, how behind the two neoliberal power there would be the same strength to impose to consciences, and most of all what would be the conse-quences of this for the possibility for social movements to try to deconstruct neoliberalism’s discourse, and to challenge it by collective action.